2013
DOI: 10.1038/bjc.2013.559
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ABO blood group in southern Chinese patients with established nasopharyngeal carcinoma

Abstract: Background:ABO blood group is associated with aetiology of nasopharyngeal carcinoma (NPC); however, the effect of it on survival of patients diagnosed with NPC has not been explored.Methods:We retrospectively analysed two cohorts of southern Chinese patients with WHO histological type III: intensity-modulated radiotherapy (IMRT) cohort, 924 patients; and conventional radiotherapy (CRT) cohort, 1193 patients. Associations of ABO blood group with survival were estimated using Cox regression.Results:In IMRT cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…In our study, however, there was no statistically significant difference among different ABO blood groups regardless of assortment. Moreover, when we only selected WHO type III patients in CRT cohort with chemotherapy history to imitate similar enrollment of the previous study (Ouyang et al, 2013), it still showed no significant difference between A and non-A blood group in terms of OS. Notably, there was basically no overlap on the selection of NPC patients between this study (year 2000-2003) and the prior study (Ouyang et al, 2013(Ouyang et al, ) (year 2003(Ouyang et al, -2006.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In our study, however, there was no statistically significant difference among different ABO blood groups regardless of assortment. Moreover, when we only selected WHO type III patients in CRT cohort with chemotherapy history to imitate similar enrollment of the previous study (Ouyang et al, 2013), it still showed no significant difference between A and non-A blood group in terms of OS. Notably, there was basically no overlap on the selection of NPC patients between this study (year 2000-2003) and the prior study (Ouyang et al, 2013(Ouyang et al, ) (year 2003(Ouyang et al, -2006.…”
Section: Discussionmentioning
confidence: 97%
“…A latest research suggested that blood type A or AB was associated with an increased risk of NPC compared with subjects with blood type O (Sheng et al, 2013). In addition, NPC patients of WHO histological type III with A blood group had significantly lower OS than those with non-A blood group (Ouyang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seemingly, the ABO blood group may be a useful prognostic factor and it also plays an important role in NPC. However, outcomes from previous studies addressing this issue remain controversial [1113] and therefore needs to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…including colon cancer, pancreatic cancer, nasopharyngeal carcinoma, esophageal cancer, breast cancer, skin cancer, renal cell carcinoma and gastric cancer [7][8][9][10][11][12][13][14]. Although the study by Lee et al established the survival of NSCLC patients who received curative surgery within the context of ABO blood group, the aim of their study was to investigate the prognostic role of expression of blood group antigen A in tumor cells [15].…”
Section: Introductionmentioning
confidence: 99%